Pengelolaan Bantuan Pangan Non Tunai (BPNT) di Kelurahan Sangiasseri - Muhammad Amar; Andi Nur Akbar; Makmur Makmur (Sekolah Tinggi Ilmu Administrasi Yappi Makassar, 2025)
The BPNT problem which eventually became the background of the research problem began when researchers were visiting one of the food distribution places in Sangiasseri Village in early February 2020, this market is one of the places where the community receives assistance, when researchers conducted research at the place where the community received assistance, researchers listened to residents' complaints where the assistance they received varied, some received IDR 300,000 and some received IDR 600,000. The community explained that the non-cash food assistance program received was usually charged by the management, there were also delays in disbursement where residents received once every three months which became a problem in the BPNT program. In its implementation, the Non-Cash Food Assistance (BPNT) program experienced inaccurate targeting where financially capable families received assistance, while poor families did not. So that the socio-economic welfare of beneficiaries has not increased Non-Cash Food Assistance (BPNT) in the socio-economic welfare of beneficiaries, researchers discuss the running of the implementation of BPNT from the Sub-district, Village, RW and RT, BPNT Facilitators, and E-Warong and present findings on obstacles in the BPNT implementation system in the welfare of underprivileged families in Sangiasseri village.